Source rock evaluation of shale intervals of the Kurra Chine Formation, Kurdistan Region-Iraq: An organic geochemical and basin modeling approach - Ayad N.F. Edilbi; Kamal Kolo; Nechirvan R. Muhammed; Salman R. Yasin; Wrya J. Mamaseni; Rivan Akram (Egyptian Journal of Petroleum)
This work reports on the source rock potential and 1D-basin modeling of the Kurra Chine Formation (Late Triassic) in Northern Iraq, northeast of Duhok province. Tectonically, the area is a part of the Zagros Fold and Thrust Belt, and within the High Folded Zone of Iraqi tectonic division. The Total Organic Carbon (TOC%) values for the shale intervals indicating a fair to good organic carbon content. The Kerogen is a mixed type II-III and III. The Tmax values displays that organic matter of Kurra Chine Formation is thermally mature and it is in main oil window. From a plot of modelled vitrinite reflectance (VR) versus time, is concluded that the organic matter of the Kurra Chine Formation entered the early oil window (EOW) in the Early Cretaceous (143 Ma) and reached the peak oil window around 130 Ma ago. During the Miocene (at 14 Ma) the organic matter entered late oil window. Modelling also indicates that the onset of oil generation was in the Early Cretaceous in which 45% conversion was achieved in the Middle Miocene. Based on the current study, the shale units of the Kurra Chine Formation can be regarded as potential source rocks that are thermally mature and capable of generating hydrocarbons; however, due to uplift and unroofing, generation of hydrocarbons has ceased at present day. Keywords: Kurra Chine, Basin modeling, Source rock, Kurdistan Region, Zagros Thrust Belt